Nonlinear behavior of FG porous cylindrical sandwich shells reinforced by spiral stiffeners under torsional load including thermal effect - Tu, Tran Minh; Thai, Duc-Kien; Hoan, Pham Van; Hoa, Le Kha (Mechanics of advanced materials and structures, 2022)
This work deals with the nonlinear behavior of sandwich cylindrical shells reinforced by spiral stiffener subjected to torsional load in the thermal environment. The sandwich cylindrical shells composed of functionally graded porous core and two functionally graded (FG) face sheets is considered for the first time. Based on the Donnell shell theory with von Karman geometrical nonlinearity in conjunction with Lekhnitskii's smeared stiffeners technique for spiral stiffeners, the governing equations are obtained. The comparisons are made with available results to show the validation of the proposed analytic approach. The effects of various shell geometrical characteristics, angle stiffeners, number of spiral stiffeners, material parameters, and temperature change are investigated.